The role of South African Broadcasting Corporation television soap operas in sustaining African traditional culture : a case study of Muvhango - Maseeme, Tricia (My University, 2021)
Culture gives identity to the people, that which should run from one generation to another. In this information age, media are expected to be carriers of culture to help sustain its transmission through generations. This case study explored the role of the South African public broadcaster in sustaining African traditional culture concerning SABC 2 soap opera named Muvhango. Data was collected through semi-structured interviews with a sample of 25 participants from Tshakhuma village in Vhembe District. The study hypothesised that there is a misrepresentation of reality in soap opera. However, the findings of the study prove that media representations about tradition are a true reflection of the culture impersonated. The results have shown that there is a good relationship between the media and culture, which the media as transmitters of culture are fulfilling. The findings of the study have proven sustainability of culture. However, thorough research is encouraged for content producers to have more accurate and truthful representation.
Thesis (M. A. (Media Studies)) -- University of Limpopo, 2021
Keywords: Culture; Soap opera; South African Broadcasting Corporation; Muvhango; African traditional culture; Television; Broadcasting; Television soap operas -- History and criticism; Television broadcasting -- South Africa; Television broadcasting -- Social aspects -- South Africa; Culture